The study of group and team management in agribusiness companies - Szabados, György (Applied Studies in Agribusiness and Commerce, 2009)
For almost three decades now that the operation of groups and teams became highlighted by scientific examinations and widespread acknowledged leverage for improving corporate efficiency and effectiveness. Much is known about general conditions of operation, still little is known about managerial attitudes, behaviour in operating them. Considering the agribusiness sector, we have hundreds of years of traditions; although operational rules, internal properties, managerial aspects are poorly acknowledged. The Department of Management of University of Debrecen has been conducting research in this field for many years now. Its research program enabled me to work out a questionnaire for surveying agribusiness organizations so that I could identify major and typical characteristics of performance groups. In this article I intend to more precisely describe internal rules, relations and characteristics of this phenomenon.